Effects of a Single Course of Prenatal Betamethasone on Dendritic Development in Dentate Gyrus Granular Neurons and on Spatial Memory in Rat Offspring - Bustamante, Carlos; Valencia, Martina; Torres, Christian; González, María José; Carvajal, Constanza; Sandoval, Denisse; Gutiérrez-Rojas, Cristian; Pascual, Rodrigo (Neuropediatrics, 2014)
Background Preterm babies treated with synthetic glucocorticoids (sGC) in utero exhibit behavioral alterations and disturbances in brain maturation during infancy. However, the effects on dentate granule cell morphology and spatial memory in rats that were given clinically equivalent doses of antenatal betamethasone remain unclear.Methods Pregnant rats were randomly divided into the following two experimental groups: control (CON) and betamethasone-treated (BET) groups. At gestational day 20 (G20), BET dams were subcutaneously injected with a 0.17 mg/kg betamethasone solution, and CON animals received a similar volume of saline. At postnatal days 22 (P22) and P52, BET and CON offsprings were behaviorally evaluated in the Y-Maze test, and the dentate gyrus granular neurons were histologically analyzed.Results Animals prenatally treated with a single course of betamethasone exhibit a significant decrement in the dendritic outgrowth of dentate granule cells along with impaired spatial memory when evaluated at P52. Moreover, the body and brain weight of the BET group was significantly lower than the CON group at P0, P22, and P52.Conclusion The current results indicate that a single course of betamethasone in pregnant rats produces significant neuronal and behavioral impairments of the offspring at adolescence along with a decrement in somatic and brain weights at each of the three ages evaluated.
Keywords: betamethasone; dendritic development; spatial memory